Comparing clinical manifestations of myocardial infarction (MI) between men and women at CCUs of hospitals affiliated to Shaheed Beheshti Medical University - Nikravan, M; Moradi, F; Maleki, M; Alavi Majd, H; Zohari Anboohi, S (Advances in Nursing & Midwifery, 2008)
Background Myocardial infarction (MI) is an irreversible necrosis of myocardium usually resulted from complete obstruction of coronary arteries and sudden disruption of blood flow and oxygen to the heart muscle. Studies suggest that, in addition to various reasons for inappropriate management of MI, one of the causes is unfamiliarity of patients and healthcare professionals including nurses regarding difference of MI manifestations in women and men leading to wastage of golden time for invasive and noninvasive measures and the resultant complications and even death. Purpose This descriptive-comparative study was conducted to identify the difference of clinical manifestations of MI in women and men hospitalized at CCUs of hospitals affiliated to Shaheed Beheshti Medical University in 2006. Methods 330 patients (165 men and 165 women) were selected by purposive sampling method. Data collection tools included an information form, a checklist, and McGill’s questionnaire. Content and face validities were determined by expert views and reliability of the tools was determined by internal consistency (r=0.86). Results No significant difference was found between the two groups in terms of demographics and quality, severity and pattern of pain (P<0.05). Men experienced more severe pain and pain along with chest discomfort than women. In contrast, pain commencement in a location other than chest, lack of pain and chest discomfort, and only chest discomfort were seen more in women than men (P0.02). Women experienced vomiting, dyspnea, fatigue/lassitude and anxiety more significantly than men while men had hiccups, perspiration and syncope more than women. Conclusion Findings showed no difference between men and women in quality, severity and pattern of MI pain. However, manifestations such as vomiting, dyspnea, anxiety, location of pain and … were different between men and women. Keywords Myocardial infarction, MI manifestations, MI in women.